Pertanggungjawaban Pidana Korporasi dalam Kejahatan Siber pada Aktivitas Bisnis Digital di Indonesia - Jamaludin; Burhanudin; AL Pyan Syah Marszedi (RETORIKA: Journal of Law, Social, and Humanities, 2026)
This study aims to analyze corporate criminal liability for cybercrime in digital business activities in Indonesia and formulate a legal framework that ensures legal certainty in enforcing corporate criminal liability. This study employs normative legal research using statutory and conceptual approaches. Legal materials consist of primary, secondary, and tertiary legal sources collected through literature review and analyzed using legal interpretation, legal theories, and legal principles. The findings indicate that corporate criminal liability for cybercrime may be imposed where there is a clear connection between the criminal act and the corporation’s interests, business activities, policies, or failure to exercise adequate supervision. Criminal acts committed by individuals within a corporate environment do not automatically establish corporate criminal liability but must be assessed based on the perpetrator’s position, the purpose of the act, the benefits obtained by the corporation, and its connection to corporate business activities. The construction of corporate criminal liability requires integration of criminal law, cyber law, and business law through clear standards concerning the basis and limits of liability. This framework provides legal certainty while encouraging secure, responsible, and integrity-based digital business governance in Indonesia